HPV Detection in Head and Neck Squamous Cell Carcinomas: What Is the Issue? - Augustin, Jeremy Gbenakpon; Lepine, Charles; Morini, Aurelien; Brunet, Anais; Veyer, David; Brochard, Camille; Mirghani, Haitham; Péré, Hélène; Badoual, Cécile (Frontiers in Oncology, 2020)
Besides classic tobacco and alcohol risk factors, Human Papillomavirus (HPV) plays a role in the development of a subset of head and neck squamous cell carcinomas (HNSCCs), and notably oropharynx squamous cell carcinomas (OPSCCs). HPV-induced OPSCCs have a different biological behavior and a better prognosis compared to non HPV-induced OPSCCs and the eight TNM classification now separates these two entities. Therefore, determining the HPV status of patients with OPSCC is now essential for treatment, prognosis and development of clinical trials. In this review, after reminding essential steps of HPV implication in cell cycle, we describe the existing tools that are currently feasible in routine practice according to facilities available in health structures, with their benefits and drawbacks: HPV PCR, E6/E7 mRNA RT-PCR, E6/E7 mRNA in situ hybridization, HPV DNA in situ hybridization, P16 immunochemistry. Besides these traditional HPV detection tools, novel diagnostic approaches are being evaluated for HPV-induced OPSCC “ultrastaging”. E6 humoral response and ddPCR detecting HPVct DNA are two techniques performed on blood and are therefore non-invasive. Baseline E6 humoral levels could have a prognostic value and HPVct DNA could be helpful for HPV OPSCC recurrence monitoring. At last, next generation sequencing (NGS) based “capture HPV” is a technique feasible on biopsies and circulating DNA material. It helps characterizing HPV integration status and sites and it could define prognostic subgroups in HPV-induced OPSCC. These novel precision detection tools could be further integrated in the care of patients with HPV-induced OPSCC.